2022
DOI: 10.2144/btn-2021-0075
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of the Chromodomain Factor MRG-1 in C. Elegans Affects Chromatin-Regulatory Dynamics

Abstract: Epigenetic mechanisms control chromatin accessibility and gene expression to ensure proper cell fate specification. Histone proteins are integral chromatin components, and their modification promotes gene expression regulation. Specific proteins recognize modified histones such as the chromodomain protein MRG-1. MRG-1 is the Caenorhabditis elegans ortholog of mammalian MRG15, which is involved in DNA repair. MRG-1 binds methylated histone H3 and is important for germline maturation and safeguarding. To elucida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 59 publications
3
10
0
Order By: Relevance
“…The above experiments, together with previous data using CFP-1 or MRG-1 as bait in IP-MS experiments (Beurton et al, 2019; Baytek et al, 2022), confirm the presence of SIN-3 in a smaller complex related to yeast and mammalian Rpd3/SIN3S (Carrozza et al, 2005b; Jelinic et al, 2011) containing ATHP-1/PHF12, MRG-1/MRG15, CFP-1 and HDA-1 as the only HDAC. In addition we identify a second complex that we will refer to as SIN3L and that contains SUDS-3, HDA-3, HDA-1, ARID-1/ARID4, NAP-1 and the transcription factor C01G6.5 (Figure 2B).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The above experiments, together with previous data using CFP-1 or MRG-1 as bait in IP-MS experiments (Beurton et al, 2019; Baytek et al, 2022), confirm the presence of SIN-3 in a smaller complex related to yeast and mammalian Rpd3/SIN3S (Carrozza et al, 2005b; Jelinic et al, 2011) containing ATHP-1/PHF12, MRG-1/MRG15, CFP-1 and HDA-1 as the only HDAC. In addition we identify a second complex that we will refer to as SIN3L and that contains SUDS-3, HDA-3, HDA-1, ARID-1/ARID4, NAP-1 and the transcription factor C01G6.5 (Figure 2B).…”
Section: Resultssupporting
confidence: 82%
“…Although SIN3L subunits alone may not be required for fertility, the observation that athp-1; hda-3 and athp-1; suds-3 double mutants are fully sterile suggests at least partial redundancy of the two complexes, or additional functions for the encoded subunits independent of SIN-3. Interestingly, while mammalian HDAC1 and HDAC2 are mostly considered to be functionally redundant, we found that both HDA-3 and HDA-1 are present in the SIN3L complex identified in this study, while SIN3S components only copurify with HDA-1 (Baytek et al, 2022;Beurton et al, 2019).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations